2010
DOI: 10.1002/cncr.25334
|View full text |Cite
|
Sign up to set email alerts
|

Quality of surgical resection for nonsmall cell lung cancer in a US metropolitan area

Abstract: The leader peptide of a recombinant MnSOD (rMnSOD‐Lp) constitutes the carrier that allows rMnSOD to penetrate tumor cells. A synthetic preparation of rMnSOD‐Lp was 68Ga labeled (rMnSOD‐Lp‐68Ga) and injected into animals bearing spontaneous mammary cancers, followed by PET examinations, which demonstrated unambiguously the tumor sites in all the animals, suggesting that if rMnSOD‐Lp was able to transport the radioisotope into tumor cells, it would also be able to deliver cytotoxic molecules. The rMnSOD‐Lp was, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 30 publications
1
42
3
Order By: Relevance
“…Allen et al [12] identified measures of good-quality surgery from NCCN guidelines and two surgical studies. Of the 746 patients who underwent surgery in Memphis, USA from 2004 to 2007, only 8.2% were completely concordant with these quality measures.…”
Section: Concordance Of Practice With Treatmentspecific Guidelinesmentioning
confidence: 99%
“…Allen et al [12] identified measures of good-quality surgery from NCCN guidelines and two surgical studies. Of the 746 patients who underwent surgery in Memphis, USA from 2004 to 2007, only 8.2% were completely concordant with these quality measures.…”
Section: Concordance Of Practice With Treatmentspecific Guidelinesmentioning
confidence: 99%
“…1,3 This problem of underuse of mediastinal lymph node sampling has been described previously. 5,21,22 Studies of patients undergoing surgery for lung cancer have shown a low rate of mediastinal lymph node biopsy. 5,22 Although there are fewer data on TBNA and EBUS underuse, surveys of pulmonologists and pulmonary fellows have shown that bronchoscopy training varies signifi cantly, and presumably, practice patterns vary accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…While, the CoC recommends that at least 10 LNs should be removed and pathologically reviewed, the European Society of Thoracic Surgeons suggests a complete mediastinal dissection of all LN stations with additional guidelines on the pathological dissection of specimens. However, these guidelines are poorly adhered to and do not necessarily reflect applicability in broader clinical practice (14). Recently, as aforementioned, a notable increase has been detected in the number of LNs assessed for clinical stage I lung cancer, and these developments have been observed across all hospital types, possibly because the impact of the z0030 trial might have been large enough to emphasize the importance of nodal assessment more broadly.…”
Section: Current Guidelines For Adequate Nodal Assessmentmentioning
confidence: 99%